Norlin Frozen Foods: otak-otak Ledang / Jamalia Parnau ... [et al.] - Parnau, Jamalia; Ahmad Jailani, Jazzlyna; Rizuan, Muhammad 'Afif Alauddin; Zawawi, Muhammad Adib Arsyad; Muhammad Razali, Syerra Syaferra (2019)
Norlin Frozen Foods is also known as Otak-otak Ledang. All their products are otak-otak based ingredients. The company has innovated their product such popia otak-otak, Bebola otak-otak, Jejari otak-otak and burger patty otak-otak apart from the usual otak-otak. Moreover, all the Otak-otak made from mix of Spanish mackerels' fish and Dorab wolf-herring fish. The company take all the fish from supplier that already been process from Ulu Tiram.